INSTAGRAM AS A STAGE FOR PREACHING: Exploring the Values of Hadith in Buya Syakur’s Sufi Advice - Sembiring, Muhammad Ismailsyah; Manik, Zulfirman (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
Buya Syakur, a cleric with a critical and often controversial preaching style, has become a widely discussed figure on social media, especially Instagram. His popularity on this platform has triggered various responses, both support and criticism from multiple groups. This study aims to examine the role of Instagram as a modern da’wah medium by exploring the values ​​of hadith in Buya Syakur’s Sufi advice spread through various accounts on Instagram. The research method used is qualitative with a content analysis approach. Data were collected by searching for relevant uploads using the hashtag #buyasyakur. The results of the study show that the advice conveyed by Buya Syakur via Instagram is in line with the core values ​​of authentic hadith. In addition to enriching modern society’s understanding of Islamic teachings, the advice also emphasizes morality and ethics from a Sufi perspective. The findings of this study confirm that Instagram has great potential as a contemporary da’wah medium that can reach a wide audience. Through a simple yet meaningful presentation, this digital da’wah not only deepens people’s understanding of Islamic teachings but also maintains the authentic values ​​of hadith as a fundamental foundation in da’wah in the digital era.